MASAC Consensus Conference: impediments to conducting clinical research in persons with haemophilia, von Willebrand's disease and rare bleeding disorders. (11th October 2012) - Koerper, M. A.; Frick, N.; Kessler, C. M.
Summary A consensus conference conducted by the Medical and Scientific Advisory Council of the National Hemophilia Foundation was held in New Orleans, LA, on November 11, 2010, to discuss the impediments to conducting clinical research in persons with haemophilia, von Willebrand's disease and rare bleeding disorders. The conference combined presentations providing academic, non‐profit and industry perspectives with periods of open discussion. The objective of this conference was to identify the many challenges involved in facilitating U.S. Food and Drug Administration approval of innovative products for these patient populations.